PENGARUH PENERIMAAN PAJAK DAERAH TERHADAP PERTUMBUHAN EKONOMI DKI JAKARTA - Yurianto Yurianto; Tantowi Akhmad (UNIVERSITAS INDRAPRASTA PGRI, 2021)
Taxes are the main source of government revenue, both central and local governments. Various ways have been done to increase revenue from this tax, including local governments through various regional tax reforms. The purpose of tax reform is to increase regional revenues from the taxation sector which will be used for the prosperity of the people through economic growth and regional development. This study aims to investigate the effect of tax revenue on economic growth in DKI Jakarta Province. The research method used is a quantitative method with data from the DKI Jakarta Province in the 1987-2019 period. Regression analysis will be used and processed with SPSS software. The result obtained from this research is that local tax revenues have a positive and significant effect on economic growth in the DKI Jakarta Province during the period 1987-2019. Regional autonomy policies also affect the economic growth of DKI Jakarta. The implication of this finding is that the sustainability of local tax revenues is needed to increase economic growth in DKI Jakarta. Local tax revenues should also be used to fund productive projects or activities so as to accelerate economic growth